El trabajo docente en la perspectiva de maestros de educación física: Análisis de algunos factores condicionantes y sus restricciones para el desarrollo de la práctica pedagógica - Rufino, Luiz Gustavo Bonatto [UNESP] (Universidade Federal do Rio Grande do Sul, 2017)
This study examines some factors conditioning and restrictions to teachers’ work in Physical Education’s pedagogical practice, based on the opinions of five teachers who participated in a continuing education process. We chose a qualitative research approach, collecting data from 16 focus groups, which were recorded, transcribed and analyzed using content analysis. The results indicated that the difficulties related to career planning and infrastructure conditions directly affect professional practice. Besides, institutional curriculum development has created new dilemmas for teachers, especially related to leadership in decision-making processes during professional actions. We concluded that teaching work has to be rethought in order to professionalize teaching. Therefore, we must look at teacher training from within, valuing teachers’ professional status and the relation that emerges from that interaction with their work.
O trabalho docente na perspectiva de professores de educação física: Análise de alguns fatores condicionantes e suas restrições para o desenvolvimento da prática pedagógica
Teaching from physical education teachers’ perspective: An analysis of some conditioning factors and their restrictions to the development of pedagogical practice
Keywords: Curriculum; Personnel development; Physical education and training; Teachers